Made in Detroit a south of 8 Mile memoir - Clemens, Paul (Doubleday, 2005)
Paul Clemens grew up in the northeast corner of Detroit, just south of the city's famed 8 Mile border. In this affectionate memoir, Clemens, born the year Detroit's first black mayor (the legendary Coleman Young) was elected, tracks his own growth to maturity against the background of the city's long decline during Young's twenty years at the helm. This is a story about being caught in the middle: about being white in a black city, urban in suburban America, blue collar in an increasingly obsolete Rust Belt, and Catholic in a place where churches close at an unprecedented pace. Sparing no one--including himself--Clemens depicts with raw authenticity and redemptive grace the realities of one city's, and one family's, recent history.--From publisher description.
Keywords: Clemens, Paul -- 1973- -- Childhood and youth; Whites -- Michigan -- Detroit -- Biography; Ethnische Identität; Ethnische Beziehungen; Weiße; Detroit (Mich.) -- Biography; Detroit (Mich.) -- Race relations; Chicago, Ill.; Biografie